2016
DOI: 10.1007/s13187-016-1000-y
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Patients with Cancer: A Determinant of the Quality of Life of Their Family Caregivers

Abstract: Cancer disrupts the quality of life of both the patients and their family caregivers. This study attempted to explore the relationship between the quality of life of cancer patients and their family caregivers and to examine whether the quality of life, age, and gender of the patients contributed to the quality of life of their family caregivers. This correlational study involved 206 pairs of participants consisting of cancer patients and their corresponding family caregivers. The European Organization for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…This impact on quality of life (QoL) may differ according to the individuals' sociodemographic and clinical characteristics. Age, gender, marital status, and the severity and duration of the disease have been extensively described as significant QoL determinants . However, other factors, such as psychobehavioral factors, may also influence self‐reported QoL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This impact on quality of life (QoL) may differ according to the individuals' sociodemographic and clinical characteristics. Age, gender, marital status, and the severity and duration of the disease have been extensively described as significant QoL determinants . However, other factors, such as psychobehavioral factors, may also influence self‐reported QoL.…”
Section: Introductionmentioning
confidence: 99%
“…duration of the disease have been extensively described as significant QoL determinants. 2 However, other factors, such as psychobehavioral factors, may also influence self-reported QoL.…”
mentioning
confidence: 99%
“…Our last hypothesis 4 referred to the responsiveness of the instrument. Shahi et al (2014) ascertained that better HRQoL of patients is aligned to better HRQoL of caregivers, and Padmaja et al (2016) found a high and significant correlation between the patients' and their family caregivers' HRQoL assessed with the same instruments. , Shilling, Matthews, Jenkins, and Fallowfield (2016), and Michels, Boulton, Adams, Wee, and Peters (2016) demand the examination of responsiveness in future research.…”
Section: Discussionmentioning
confidence: 98%
“…confirmed this in the revalidation of the CQOLC. H4: According to Padmaja, Vanlalhruaii, Rana, Tiamongla, and Kopparty (2016), it is expected that correlations between change scores of the caregivers' HRQoL and the patients' HRQoL correlate at least moderately positively in between the three time points. We understand change scores as the difference of the CQOLC scores between two of the three points in time in each case.…”
Section: H1mentioning
confidence: 99%
“…In light of the poor prognosis associated with advanced HCC, there is a need to prioritize patient centered outcomes such as quality of life (QoL). Particularly, there is a strong evidence base regarding the prognostic value of health-related quality of life (HRQoL), the patients’ individual perception about their life in regards to goals, standards and concerns, and expectations with respect to their diagnosis, in the oncological setting [46,47,48,49,50,51,52]. In spite of this knowledge, there is a paucity of published data evaluating the impact of FDA-approved therapeutics on patient-centered outcomes such as HRQoL for those patients included in advanced HCC clinical trials.…”
Section: Quality Of Lifementioning
confidence: 99%